Assessing performance validity during attention-deficit/hyperactivity disorder evaluations: Cross-validation of non-memory embedded validity indicators. Issue 5 (4th July 2022) - Ausloos-Lozano, Jenna E.; Bing-Canar, Hanaan; Khan, Humza; Singh, Palak G.; Wisinger, Amanda M.; Rauch, Andrew A.; Ogram Buckley, Caitlin M.; Petry, Luke G.; Jennette, Kyle J.; Soble, Jason R.; Resch, Zachary J.
ABSTRACT: Embedded performance validity tests (PVTs) are key components of neuropsychological evaluations. However, most are memory-based and may be less useful in the assessment of attention-deficit/hyperactivity disorder (ADHD). Four non-memory-based validity indices derived from processing speed and executive functioning measures commonly included in ADHD evaluations, namely Verbal Fluency (VF) and the Trail Making Test (TMT), were cross-validated using the Rey 15-Item Test (RFIT) Recall and Recall/Recognition as memory-based comparison measures. This consecutive case series included data from 416 demographically-diverse adults who underwent outpatient neuropsychological evaluation for ADHD. Validity classifications were established, with ≤1 PVT failure of five independent criterion PVTs as indicative of valid performance (374 valid performers/42 invalid performers). Among the statistically significant validity indicators, TMT-A and TMT-B T-scores (AUCs = .707-.723) had acceptable classification accuracy ranges and sensitivities ranging from 29%-36% (≥89% specificity). RFIT Recall/Recognition produced similar results as TMT-B T-score with 42% sensitivity/90% specificity, but with lower classification accuracy. In evaluating adult ADHD, VF and TMT embedded PVTs demonstrated comparable sensitivity and specificity values to those found in other clinical populations but necessitated alternate cut-scores. Results also support use of RFIT Recall/Recognition over the standard RFIT Recall as a PVT for adult ADHD evaluations.